Cognitive impact in bipolar disorder - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2019)
It appears that bipolar patients suffer from cognitive difficulties whereas they are in period of thymic stability. These intercritical cognitive difficulties are fairly stable and their severity is correlated with the functional outcome of patients. Nevertheless, the profile of cognitive impairment varies significantly from study to study quantitatively and qualitatively. According to the studies, the authors find difficulties in terms of learning, verbal memory, visual memory, working memory, sustained attention, speed of information processing, functions executive. On the other hand, deficits of general intelligence, motor functions, selective attention, and language are not usually found. One of the reasons for the heterogeneity of results is the difficulty of exploring cognition in bipolar disorder. Many factors must be taken into account, such as the presence of residual mood symptoms, the longitudinal history of the disorder (age of onset, number of episodes due, among others, the neurotoxic impact of depressive episodes and deleterious cognitive effects). (length of hospitalization), level of disability severity, comorbidities (particularly addictive).